Advances on Molecular Mechanism and Clinical Treatment in Invasive Mucinous Adenocarcinoma - Minjun SHI; Bo YE (Chinese Journal of Lung Cancer)
Invasive mucinous adenocarcinoma (IMA) is a special type of lung adenocarcinoma that accounts for 2% to 10% of all lung adenocarcinoma. Surgical treatment is preferred for IMA, and traditional chemotherapy drugs and targeted therapy drugs have poor efficacy in this disease. IMA has unique prognostic, imaging and molecular features. The incidence of IMA is very low, so thoracic surgeons may lack of knowledge to the disease and misdiagnose it as benign diseases such as pneumonia and tuberculosis. This article reviews and discusses the imaging, clinicopathological features, treatment methods and prognosis of IMA.